Optimization of Integrated Design of Wastewater Treatment and Sanitary Sewer Network Using Ant Colony Optimization Algorithm - Ramtin Moeini; Mohammadhadi Afshar (آب و فاضلاب, 2014)
In this paper a heuristic method with ad-hoc engineering concept is proposed for design optimization of integrated wastewater treatment and sanitary sewer network using ant colony optimization algorithm. The optimal design of integrated wastewater treatment and sewer network requires that the wastewater treatment location, layout and size of sewer network are optimally determined. The problem of finding the optimal design of integrated wastewater treatment and sanitary sewer network is an expensive task that should be formulated as an optimization problem if an optimal least cost design is required. This problem is a highly constrained Mixed-Integer Nonlinear Programming (MINLP) problem presenting a challenge even to conventional methods. In this paper an efficient heuristic method with ad-hoc engineering concept using ant colony optimization algorithm is proposed and used to solve hypothetical test example and the results are presented and compared with those of obtained with using genetic algorithm.  The results indicate the effectiveness and efficiency of the proposed method to optimally solve the problem of optimal design of integrated wastewater treatment and sewer network.